MODIFICATION OF TECHNOLOGY ACCEPTANCE MODEL OF THE USE OF M-BANKING IN SMALL MEDIUM ENTERPRISES IN KUDUS DISTRIC USING A STRUCTURAL EQUATION MODELLING - Tania Ivanka Anggraini; Rangga Primadasa; Vikha Indira Asri (Journal of Industrial Engineering Management, 2023)
This study aims to determine the acceptance of MSME technology in the Kudus Regency in using electronic payment service technology or e-payment as a payment method. The method used is Technology Acceptance Model 3 (TAM 3). Identify acceptance of m-banking using a questionnaire given to owners and employees. Analyze by testing the hypothesis of m-banking acceptance data by testing validity, and reliability and proceed to test using the Structural Equation Modeling (SEM) method. The results of the test show that 5. Owners and employees of MSME actors in the Kudus Regency can accept the use of m-banking in carrying out any performance because it makes it easier when there is a time of urgency.